Shaker Exercise in Dysphagia Rehabilitation for Myasthenia Gravis Patients - Andreas Wardono Santoso; Vitriana (Indonesian Journal of Physical Medicine & Rehabilitation, 2014)
Objective: To evaluate whether Shaker Exercise can improve dysphagia in MG patients.Methods: Pre-Post test design. Ten patients with a confirmed diagnosis of MG (Osserman class IIB) were recruited for this study. All patients did Shaker exercise an hour after taking their medication,with holding time and repetition which increased gradually for 6 weeks. Examinations using Fiber Optic Endoscopic Evaluation of Swallowing (FEES) and Eating Assessment Tool (EAT-10) wereconducted in between.Results: All patients completed 6 weeks of exercise with increased holding time (pre 14±6.11; post 27.5±4.25) and repetition (pre 12.7±6.9; post 20.7±7.75). Only one patient experienced discomfortin their neck muscles. Pre intervention FEES Examination showed that all ten patients have residue (100%), two have spillage (20%), three have penetration risk (30%) and two have aspiration risk(20%). Post intervention showed no residue in seven patients, while three showed decreased residue (70%; 30%; 100%). There was no spillage, penetration risk or aspiration risk in all patients. Pre(11.1±9.386) and post (2.2±2.573) intervention EAT-10 scores show significant improvement (p=0.002).Conclusion: Shaker Exercise can be used safely to improve dysphagia in Myasthenia Gravis patients.Keywords: Myasthenia Gravis, Shaker Exercise, Dysphagia